Sosialisasi Penggunaan Media Sosial kepada Peserta Peelatihan Menjahir di Balai Latihan Kerja Dinas Ketenagakerjaan Kota Palembang - Muhammad Bahrul Ulum; Ayu Geby Gisela Syaputri (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Social media exists and has become a part of human life. The presence of the internet and its development brings new ways of communicating in social life. Social media presents and changes the paradigm in communication in today's society. Communication in social media is not limited by distance, time and space. It can happen anywhere, anytime, without having to meet face to face. Even social media can seem to negate social status which often becomes a barrier in communication. Indonesia with a population of 256.4 million people, as many as 130 million people or around 49 percent of whom are active users of social media. According to research conducted by “We Are Social”, the social media that Indonesians are currently interested in are Youtube, Facebook, Instagram, and Twitter. Based on the information contained in wartakota, Indonesia is the largest Instagram user community in Asia Pacific with 45 million active users out of a total global user of 700 million people. Currently some social media are not only used as a means of satisfying entertainment needs, in addition to being social media that is in great demand, especially Instagram, Instagram is also a social media that has enormous opportunities in business activities. For aspiring entrepreneurs, social media is a fairly effective marketing tool because it is cheap and can be seen by all social media users. This will certainly make it easier for sewing training participants at Balai Latihan Kerja Dinas Ketenagakerjaan Kota Palembang who may wish to become entrepreneurs in the future.